NEW STUDENT ADMISSIONS APPROACH BASED ON EDUCATIONAL ISLAMIC SERVICE QUALITY - Pamungkas, Sahril Dwi; Aldo Redho Syam; Syamsul Arifin (Jurnal Manajemen Pendidikan, 2025)
This research aims to explore student recruitment strategies based on the quality of Islamic educational services and their implications. Using a descriptive qualitative approach with a case study design, data were obtained through in-depth interviews, observations, and documentation. Data was analyzed using the Miles & Huberman interactive model, with service quality strategies analyzed through five ServQual dimensions that were reconceptualized within an Islamic values framework, measured using core service indicators whose results were then contextualized for their ethical accountability with Islamic values. Research findings indicate that incorporating Islamic values into ServQual dimensions produces progressive and comprehensive service strategy formulations. This approach successfully constructs a holistic educational ecosystem that is adaptive to students' academic, spiritual, and emotional needs. This research also presents recommendations for a comprehensive approach in measuring Islamic values-based educational service quality mechanisms. Strategic implications of this implementation include improvements in both academic and non-academic student achievement, an inclusive learning environment, strengthened institutional reputation, increased stakeholder satisfaction, and consistent increases in the number of applicants.